The effect of spinach supplementation on exercise-induced oxidative stress - Bohlooli, S.; Barmaki, S.; Khoshkhahesh, F.; Nakhostin-Roohi, B. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: Nutritional supplements have been very popular among athletes and individuals. Spinach is an important dietary vegetable rich in antioxidants which is commonly consumed. This study was conducted to assess the effects of chronic daily spinach supplementation on known markers of oxidative stress and muscle damage following half-marathon in well-trained healthy young men.